Joseph Brodsky and the visual arts: consumer, practitioner, interpreter - Xenophontos, P (2021)
Joseph Brodsky (1940–1996) was a highly visual writer. This thesis looks at his poems and essays, and a range of unpublished archival documentation to argue that he was an individual sensitive to visual stimuli in his environments, whose texts are in dialogue with non-literary worlds as much as they are with literary ones. More generally, I foreground the importance of looking at literary texts from non-literary points of view.